2010
DOI: 10.1108/09600031011079319
|View full text |Cite
|
Sign up to set email alerts
|

Coordination in humanitarian logistics through clusters

Abstract: Access to the published version may require subscription. N.B. When citing this work, cite the original published paper. Permanent link to this version:http://urn.kb.se/resolve?urn=urn:nbn:se:hj:diva-13806 1 COORDINATION IN HUMANITARIAN LOGISTICS THROUGH CLUSTERS ABSTRACT Purpose of this paperIn the field of humanitarianism, cluster thinking has been suggested as a solution to the lack of coordinated disaster response. Clusters for diverse functions, including sheltering, logistics and water and sanitation, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
117
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(126 citation statements)
references
References 32 publications
1
117
0
3
Order By: Relevance
“…Natural disaster Jahre & Heigh, 2008;McLachlin et al 2009;Charles, 2010;Gatignon et al 2010;Jahre & Jensen, 2010;Oloruntoba, 2010;Duran et al 2011;Pedraza Martinez et al 2011;Cozzolino et al 2012;Pedraza Martinez & Van Wassenhove, 2013;Buddas, 2014;Ergun et al 2014;Scholten et al 2014;Gralla et al 2015;Jahre & Fabbe-Costes, 2015;Stauffer et al 2015;War/terrorism Listou, 2008McLachlin et al 2009;Choi et al 2010;Jahre & Jensen, 2010;McCoy et al 2011;Pedraza Martinez et al 2011;Cozzolino et al 2012;Pedraza Martinez & Van Wassenhove, 2013;Besiou et al 2014;Buddas, 2014;Eftekhar et al 2014;Gralla et al 2015;Kunz et al 2015 Jahre & Heigh, 2008;Listou, 2008;Charles, 2010;Gatignon et al 2010;Duran et al 2011 ;Pedraza Martinez et al 2011;Besiou et al 2014;Buddas, 2014;Gralla et al 2015;Gralla et al 2015;Jahre & Fabbe-Costes, 2015;Stauffer et al 2015;Jahre et al 2016 Manufacturing risk factors Supply ris...…”
Section: Type Of Risk Reference Abnormalunclassified
“…Natural disaster Jahre & Heigh, 2008;McLachlin et al 2009;Charles, 2010;Gatignon et al 2010;Jahre & Jensen, 2010;Oloruntoba, 2010;Duran et al 2011;Pedraza Martinez et al 2011;Cozzolino et al 2012;Pedraza Martinez & Van Wassenhove, 2013;Buddas, 2014;Ergun et al 2014;Scholten et al 2014;Gralla et al 2015;Jahre & Fabbe-Costes, 2015;Stauffer et al 2015;War/terrorism Listou, 2008McLachlin et al 2009;Choi et al 2010;Jahre & Jensen, 2010;McCoy et al 2011;Pedraza Martinez et al 2011;Cozzolino et al 2012;Pedraza Martinez & Van Wassenhove, 2013;Besiou et al 2014;Buddas, 2014;Eftekhar et al 2014;Gralla et al 2015;Kunz et al 2015 Jahre & Heigh, 2008;Listou, 2008;Charles, 2010;Gatignon et al 2010;Duran et al 2011 ;Pedraza Martinez et al 2011;Besiou et al 2014;Buddas, 2014;Gralla et al 2015;Gralla et al 2015;Jahre & Fabbe-Costes, 2015;Stauffer et al 2015;Jahre et al 2016 Manufacturing risk factors Supply ris...…”
Section: Type Of Risk Reference Abnormalunclassified
“…Information detailing the situation of roads and highways, the number of people affected and the resource requirements (human, material, equipment, and food) is necessary to provide aid to the beneficiaries. Jahre & Jensen (2010) reported that logistics is particularly crucial at the beginning of a crisis or disaster due to regular infrastructure disruption (for instance, seeing which roads and vehicles are still operational). Balcik et al (2010) reported that uncertainty associated with the disaster and a lack of resources (financial, human, technological and information) creates great difficulty in coordinating humanitarian aid activities.…”
Section: Multi-criteria Analysismentioning
confidence: 99%
“…Within the literature (Heaslip et al, 2012;Jahre and Jensen, 2010;Kovács and Spens, 2007;Listou, 2008), there is agreement that different operations can be distinguished in the times before a disaster strikes (the preparation phase), instantly after a disaster (the immediate response phase) and in the aftermath of a natural disaster (the reconstruction phase). Not surprisingly, different logistical requirements, resources and skills are needed for the three distinct phases of disaster relief.…”
Section: Phases In Humanitarian Reliefmentioning
confidence: 99%
“…This in turn will have an impact on the logistics response. One of the identifiable trends is the increasing need for agility (adaptability) of military logistical support, with less emphasis on buffer stock and more on manoeuvrability (Heaslip et al, 2012;Jahre and Jensen, 2010). Effectively, this means that agility and scale need to be separated.…”
Section: Proposed Modelmentioning
confidence: 99%
See 1 more Smart Citation